Considerações sobre o curso de Pós-Graduação da FAUUSP - 1973-1999 - Katinsky, Júlio Roberto (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2000)
The course of Architecture and Urbanism of the University of São Paulo, inaugurated in 1948, embraced a double aim as defined by Anhaia Mello, Artigas, Cintra do Prado and others, and greatly influenced by Lucio Costa and Mário de Andrade. The founding fathers sought both to meet the technical or technological concerns of the building industry as well as take into account the suggestions of artists committed to the llluminism ideals of liberty, such as the architects Boullée and Durand or the poets Shiller and Goethe. Keeping its roots alive, during its fifty years, the undergraduate course has been characterized by the emphasis put not on the real city, but on the city to be constructed, on the utopian ideal city, on the city to be proposed. This paper argues that the same principles should be maintained as guiding lines for the graduate course